2022
DOI: 10.18203/2349-3259.ijct20222960
|View full text |Cite
|
Sign up to set email alerts
|

Τhe effect of task oriented approach on gait of hemiplegic patients: a case series study

Abstract: <p>The last few years, the main purpose of the treatment of the hemiplegic patient, is to regain his ability to execute functional activities of daily living independently. According to the latest studies, the effectiveness as well as the importance of task-oriented approach (TOA), is apparent and determining to reacquire the patient’s lost independency, through the practice of the specified functional activities. The aim of this study is to investigate a program of TOA on gait of hemiplegic patients. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Perhaps the treadmill exercise program was not as successful, even though it targeted the patient's functional gait, due to the patient's failure to be demarcated into specific rehabilitation frameworks based on symptoms. Also, the task-oriented approach program that was used in a case study showed very positive results for gait and balance in stroke patients [23]. Overall, in combination with the case studies, gait and balance exercise programs improve a patient's functionality, thereby achieving his/her independence in ADLs and reducing his/her symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…Perhaps the treadmill exercise program was not as successful, even though it targeted the patient's functional gait, due to the patient's failure to be demarcated into specific rehabilitation frameworks based on symptoms. Also, the task-oriented approach program that was used in a case study showed very positive results for gait and balance in stroke patients [23]. Overall, in combination with the case studies, gait and balance exercise programs improve a patient's functionality, thereby achieving his/her independence in ADLs and reducing his/her symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…The application of GDT only (control group) in this study has a positive effect on functional performance and balance, which is consistent with previous research on stroke patients. Previous studies have found that training tailored to the specific task (GDT), based on research from rehabilitation science, motor learning, and motor control, is more effective in improving the functionality and the overall quality of life for post-stroke patients compared to traditional treatments (13,(18)(19)(20)(21)].…”
Section: Discussionmentioning
confidence: 99%